Drivers of Local Government Budget Performance: The Moderating Role of Economic Growth in Indonesia - Imelda Andrianty; Haryadi Haryadi; Sri Rahayu; Enggar Diah Puspa Arum; Rico Wijaya (Greenation International Journal of Economics and Accounting, 2026)
Budget performance has become a crucial indicator of accountability and effectiveness in local government financial management. Despite extensive discussions on public sector budgeting, empirical evidence on the determinants of budget performance and the role of regional economic conditions remains limited. This study investigates the drivers of local government budget performance and examines the moderating role of economic growth in Indonesia. The study employs balanced panel data from 11 local governments in Jambi Province covering the period 2016–2024, resulting in 99 observations. This analysis applies a panel data regression approach to conclude the relationship between fiscal management variables and budget performance. The findings reveal that budget commitment has a significant negative effect on budget performance, whereas budget absorption has a positive and significant effect. In contrast, budget politics does not significantly influence budget performance. Furthermore, economic growth plays a significant moderating role in the relationship between fiscal management variables and budget performance. The moderating model demonstrates stronger explanatory power than the baseline model. These results highlight the importance of regional economic conditions in shaping the effectiveness of public financial management and improving local government budget performance.